A Three – Step – One Mapping Iterative Scheme for Multi-Valued Maps in W-Hyperbolic Space - Hani Abdulameer Ibrahim; Wasan Talib Hassan (Eximia, 2024)
In this paper firstly we introduce A Three – Step – One Mapping Iterative scheme for multivalued mapping in W-Hyperbolic space secondly we prove a convergence result of A Three – Step – One Mapping Iterative Scheme for multivalued nonexpansive mapping in the same space also established the convergence results when use Condition and by using Hemicompact mapping in uniformly W-Hyperbolic space